PENGARUH MODEL PEMBELAJARAN READ, ANSWER, DISCUSS, EXPLAIN, CREATE (RADEC) BERBANTUAN MEDIA KOMIK DIGITAL TERHADAP KETERAMPILAN BERPIKIR TINGKAT TINGGI (HOTS) SISWA PADA MATERI PERUBAHAN LINGKUNGAN - Ariq Nabil Abdillah; Poppy Anggraeni; Ai Hayati Rahayu (Sebelas April Elementary Education, 2025)
This research is motivated by the low level of high-order thinking skills of students who are characterized by not being active in analyzing, evaluating, and discussing. The purpose of this research is to determine the effect of the RADEC learning model assisted by digital comic media on the high-order thinking skills of fifth-grade students of SDN Pakuwon II, South Sumedang District, Sumedang Regency in the 2024/2025 academic year in the field of environmental change. The method used in this research is Pre-Experimental with a pre-experimental research design of one group pretest-posttest design. The population in this research is fifth-grade students of SDN Pakuwon II, using all 12 members of class V. Data collection techniques in this research are non-test and test techniques. The research instruments are observation sheets for model implementation and high-order thinking skills test sheets. Based on the results of the study, it shows that the average pretest value (52.50) and the average posttest value (83.33) show the results of the data analysis obtained where the sig value (2-tailed) is 0.00 < (α = 0.05), then H₁ is accepted and the effect size test value is 2.45 which indicates high. So it can be concluded that there is an influence of the application of the RADEC learning model assisted by digital comic media on the high-level thinking skills of class V students of SDN Pakuwon II, South Sumedang District, Sumedang Regency, 2024/2025 Academic Year on environmental change material.